In Vitro Susceptibility of Lefamulin Against Staphylococcus Aureus Isolated from Clinical Samples in a Tertiary Care Hospital - Bushra, Riffat; Naqvi, Sakeenah Hussain; Mirza, Irfan Ali; Imtiaz, Anam; Sajjad, Rabia; Gill, Maria Mushtaq (Pakistan Armed Forces Medical Journal, 2025)
Objective:To determine in vitro susceptibility of Lefamulin against Staphylococcus aureus isolated from respiratory samples in a tertiary care hospital in Pakistan.Study Design: Cross sectional study.Place and Duration of Study: Department of Microbiology Armed Forces Institute of Pathology, Rawalpindi, Pakistan from  Jan to Jun 2022.Methodology: The respiratory samples comprising of sputum, nasobronchial lavage (NBL), endobronchial washings (EBW) of patients were included in the study. The samples were processed at the Microbiology department laboratory using the standard microbiological procedures. The inoculation and incubation of specimens were done as per standard guidelines. The S. aureus isolates were identified on the basis of colony morphology, gram staining, Catalase, Coagulase and deoxyribonucleic acid-ase (DNAase) test.Data was analysed using Statistical Package for Social Sciences (SPSS) 21.0. Frequencies and percentages were calculated for all quantitative variables.Results: 215 specimens were evaluated, out of which 210(98.6%) were sensitive to Lefamulin. Out of these sensitive 212(98.6%) isolates 80(37.2%) belonged to EBW, 80(37.2%) from BAL, 40 (18.6%) from NBL and 15(7.0%) were sputum samples which were all sensitive.Conclusion: This study showed that 98.6% of S. aureus were sensitive to Lefamulin antibiotic.